Linear loci: reviving nature impulse at Jalan Raja Chulan - Ramlan, Nor Hidayah; Abdul Malek, Nurhayati; Zen, Ismawi (Kulliyah of Architecture & Environmental Design, International Islamic University Malaysia, 2019)
Character of city or urban area is important as it influences the perception of residents, visitors and business. Vibrant city provides a sense of arrival that introduces and highlights the city’s character, identity and capacity. However, uncontroll planning and development can contribute to the loss of character and identity, leaving the area unattractive and passive. The design seeks a solution to enhance the streetscape design and create public spaces along 500m from road junction (Jalan Raja Chulan and Jalan Sultan Ismail) towards the entrance of Bukit Nanas Reserve Forest, with bold and thematic design but without neglecting the value of local characters.